Pengelolaan Anggaran Produksi Film Hybrid: Implementasi Production Triangle Pada Film Maya Can’t Have Nice Things - Ariel, Stefanie; Sitepu, Petrus Damiami (Titik Imaji, 2026)
The film Maya Can’t Have Nice Things utilizes the hybrid method in the production process, combining live-action and animation elements to create production cost efficiency. In budget management, the producer plays a crucial role by implementing the production triangle concept, prioritizing cheap and good in strategic decision-making. The producer collaborates with other departments to optimize resources, such as using one location for multiple sets, borrowing props, and integrating animation to reduce physical set costs. Additionally, the producer plays a creative role to ensure the director's vision is achieved in the film. The use of CGI technology allows for the replacement of expensive visual elements, providing artistic flexibility without sacrificing visual quality. Although there are unforeseen costs, the budget management remains aligned with the initial production budget, even allowing for the allocation of surplus funds to other departments that support the film's creativity. Thus, the implementation of the hybrid method, along with adaptive and efficient production budget planning, demonstrates that the producer can maintain a balance between low cost and high quality, which is key to the success of independent film production.